THE INFLUENCE OF WORK-FAMILY CONFLICT ON TURNOVER INTENTION MEDIATED BY JOB SATISFACTION AND JOB STRESS (STUDY ON EMPLOYEES OF PT. PEGADAIAN GALERI24 AREA JAVA) - Fayya Marietza Hidayah; Noermijati; Armanu (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Abstract This research aims to empirically test and prove the influence of work-family conflict on turnover intention, mediated by job satisfaction and job stress (Study on employees of PT. Pegadaian Galeri24 Java Area). This type of research uses explanatory research with survey methods and a quantitative approach. The population in this study were all employees of PT. Pegadaian Galeri24 is assigned to the Java area covering East Java, West Java and Central Java, totaling 110 employees. Because the sample size for this research is not large, the author took the entire population, namely 110 employees at PT. Pegadaian Galeri24 to get a better level of accuracy. The analytical method to answer the hypothesis proposed in this research is Smart Partial Least Square (SmartPLS) Version 4.0. The results of this research show that job satisfaction mediates the influence of work family conflict on turnover intention. A large workload accompanied by long working hours will make PT employees. Pegadaian has difficulty fulfilling the needs of his role in the family. Sometimes complaints will arise from family members because of the lack of time given to the family, resulting in conflicts within the family. This conflict causes a person to not focus on their work and not be able to work optimally. He couldn't get job satisfaction, so he started looking for another job. And work stress mediates the positive influence of work family conflict on turnover intention. Complaints from family regarding lack of time for family will make someone not focus on work. The higher the conflict between work and family, the higher the work stress level of PT employees. Galeri24 pawnshops on companies have increased. Where a high level of work family conflict will encourage the emergence of high work stress so that in this situation employees feel pressured and turnover intention arises.